Land and property resources of agricultural enterprises in the system of their resource potential - Humennyi, Mykhailo Ivanovych (Національний технічний університет "Харківський політехнічний інститут", 2024)
The article is devoted to the justification of the organizational and economic principles of management and rational use of land and property resources and the determination of the principles of their effective combination based on the study of modern determinants of the development of the resource potential of agrarian enterprises. The meaning and role of property resources in the activity of agricultural enterprises are revealed, and their components and importance for ensuring the technical base and efficient production processes are defined. It is substantiated that the modernization of the technical park and the improvement of technological processes help to ensure the competitiveness of agricultural enterprises, reducing costs and increasing the quality of products. Land and property resources are defined as the basis of the resource potential of agrarian enterprises, and their proper management and continuous improvement are critical factors of enterprises' sustainable development in the modern conditions of the market environment. The need for a complex approach to managing land and property resources, which considers the specifics of the industry, regional features, and modern trends, has been proven. A comprehensive approach to effectively managing agricultural enterprises' land and property resources is considered. The importance of developing development strategies, implementing advanced technologies, and improving staff qualifications is substantiated. It is noted that strategies such as crop rotation, agroecological monitoring, energy efficiency, and digitalization can be used to optimize the use of resources. These measures contribute to increasing the efficiency of agricultural enterprises in modern conditions. It is established that the context of the land use management system should pay special attention to the basic principles crucial for its effectiveness. Scientific approach, objectivity, economic justification, availability of feedback, consideration of regional specifics, and differentiated application to different types of land stand out among the main principles.

Стаття присвячена обґрунтуванню організаційно-економічних засад управління та раціонального використання земельних і майнових ресурсів, та визначенню принципів їх ефективного поєднання на основі дослідження сучасних детермінант розвитку ресурсного потенціалу аграрних підприємств. У Розкрито значення та роль майнових ресурсів у діяльності аграрних підприємств, визначено їх складові та важливість для забезпечення технічної бази та ефективних виробничих процесів. Обґрунтовано, що модернізація технічного парку та удосконалення технологічних процесів допомагають забезпечити конкурентоспроможність аграрних підприємств, знижуючи витрати та підвищуючи якість продукції. Земельні та майнові ресурси визначено як основу ресурсного потенціалу аграрних підприємств, а їх правильне управління та постійне удосконалення визначено як ключові фактори стійкого розвитку підприємств у сучасних умовах ринкового середовища. Доведено необхідність необхідність комплексного підходу до управління земельними та майновими ресурсами, що враховує специфіку галузі, регіональні особливості та сучасні тенденції. Розглянуто комплексний підхід до ефективного управління земельними та майновими ресурсами аграрних підприємств. Обґрунтовано важливість розробки стратегій розвитку, впровадження передових технологій та підвищення кваліфікації персоналу. Зазначено, що для оптимізації використання ресурсів можна застосовувати такі стратегії, як ротація культур, агроекологічний моніторинг, енергоефективність та цифровізація. Ці заходи сприяють підвищенню ефективності аграрних підприємств у сучасних умовах. Встановлено, що контексті системи управління землекористуванням слід звернути особливу увагу на основні принципи, які мають вирішальне значення для її ефективності. Серед основних принципів виділяються науковий підхід, об’єктивність, економічна обґрунтованість, наявність зворотного зв’язку, врахування регіональної специфіки та диференційоване застосування до різних типів земель.
Земельно-майнові ресурси сільськогосподарських підприємств в системі їх ресурсного потенціалу
Keywords: land resources; property; resource potential; combining resources; strategic management; земельні ресурси; майно; ресурсний потенціал; комбінування ресурсів; стратегічне управління